Occupational Safety Practice of Hazardous Health-care Waste Management in Bengkulu City - Suyanto, Jipri; Rahmadhani, Wulan; Hilinti, Yatri; Nobnorb, Nipaporn; Phu MD, Phan Trieu (Disease Prevention and Public Health Journal, 2021)
Background: Facing many patients while the workers were limited prompted health workers to make a quick decision regarding health-care waste. High workload pressured health workers and put them at risk of getting diseases than others, especially diseases from medical waste that they took care. Besides, as health workers, they should be clean from bacteria or viruses that can transmit  diseases to their patients. This research aimed to investigate the factors associated with occupational safety practice of hazardous health-care waste management in Bengkulu City. Method: This cross-sectional study used a stratified random sampling technique to select 230 respondents who work as health workers to respond to a questionnaire interview. The data were analyzed using multivariate logistic regression to find the association between the outcomes and the independent variables. Results: The prevalence of   poor  occupational safety practice of hazardous health-carewaste management was 35.21 % (95% CI = 29.27-41.66).  The factors significantly associated with occupational safety practice of hazardous health-care waste management were; gender (p-value < 0.001), department/unit (p-value < 0.001), knowledge (p-value < 0.001), and spirituality (p-value  < 0.001). Conclusion:  gGnder, department/unit, knowledge, and spirituality were associated with occupational safety practice of hazardous health-carewaste management in Bengkulu City.